+0

# A sequence is defined recursively by the formula f(n + 1) = f(n) + 3 . The first term of the sequence is –4. What is the next term in the se

0
3431
2
+8

A sequence is defined recursively by the formula f(n + 1) = f(n) + 3 . The first term of the sequence is –4. What is the next term in the sequence?

EyasiaJ  Jun 17, 2015

#2
+26402
+10

Or just:

f(1) = -4

f(2) = f(1) + 3   so f(2) = -4 + 3  or f(2) = -1

Alan  Jun 17, 2015
Sort:

#1
+10

using notation is just a fancy way of describing a sequence.

is the number you're currently at, so with that logic n+1 is the term after it in the sequence.

f(n) is the function using n as the input.

so you know that the first term of the sequence is -4, or f(n)= -4.

In order to find f(n+1) plug in what you know for f(n).   $${f}{\left({\mathtt{n}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right)} = {f}{\left({\mathtt{n}}\right)}{\mathtt{\,\small\textbf+\,}}{\mathtt{3}}$$ we know that f(n) = -4, so it is substituted in to the equation given. $${f}{\left({\mathtt{n}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right)} = {\mathtt{\,-\,}}{\mathtt{4}}{\mathtt{\,\small\textbf+\,}}{\mathtt{3}}$$ now simplify! $${f}{\left({\mathtt{n}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right)} = -{\mathtt{1}}$$   hope this helps!
Guest Jun 17, 2015
#2
+26402
+10

Or just:

f(1) = -4

f(2) = f(1) + 3   so f(2) = -4 + 3  or f(2) = -1

Alan  Jun 17, 2015

### 9 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details